The Silent Epidemic: Surgical Site Infections and Antimicrobial Resistance - Prof. Jawaid Naeem Qureshi (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
Surgical Site Infections (SSIs) remain one of the most common and costly complications of surgery. Despite decades of advances in surgical safety, infection prevention, and antimicrobial therapy, they continue to undermine outcomes, particularly in low- and middle-income countries. The growing shadow of antimicrobial resistance (AMR) has only made this challenge more difficult, turning once-manageable infections into life-threatening conditions. This editorial reflects on the burden of SSIs, the ways AMR is reshaping their management, and the urgent steps needed, including but not limited to stronger prevention, smarter antibiotic use, and global collaboration, to protect the future of safe surgery.